Exploring students' creative thinking processes in solving non-routine mathematical problems - Mohammad Kholil; Nur Faizah; Anis Hidayati; Chanda Chansa Thelma (EDUCARE Journal of Primary Education, 2025)
Creative thinking is an essential 21st-century skill that plays a significant role in mathematics learning, especially when students encounter non-routine problems. Unfortunately, learning practices still predominantly use routine questions that emphasize algorithmic procedures, limiting students’ opportunities to develop their creative potential. This study aims to analyze the types of creative thinking students employ when solving non-routine mathematical problems and to describe their cognitive characteristics. Using an exploratory qualitative approach and a case study design, the research involved 108 eighth-grade students, with three representative subjects selected for analysis through written tests and in-depth interviews. The findings reveal variations in students’ creative thinking in solving non-routine math problems. Most (48.15%) are replicative, imitating solutions with limited flexibility; 37.96% are adaptive, adjusting strategies to context; and 13.89% are constructive, creating original solutions independently. This highlights the need for non-routine problems, creativity-based learning, and STEM integration to enhance flexibility, advanced creativity, and contextual analytical skills. The study contributes by demonstrating how non-routine problems and creativity-focused, STEM-integrated learning can cultivate diverse creative thinking types, enhance cognitive flexibility, and foster students’ ability to generate original, contextually informed solutions in mathematics education.